X-ray hysterosalphingography: the most painful part in the Nigerian woman (2011)
Background.Hysterosalphingography(HSG)despite the accompanying pain still remains relevant in gynaecological practice.For effective analgesia.it is important to ideutifv the most painful step of this procedure .Numerical Rating Scale(NRS) and the Categorical Pain Scale(CPS) were used to identify the most painful step of HSG procedure and to find out if age,parity and the degree of infertility affect pain perception in this group of patients.Patients and Methodology: Ninety Four women referred for HSG due to infertility were recruited into this study.Their background pain and perceived pain of each step of the procedure was graded using the NRS and the CPS. The data collected were statistically analvsed. Results:Participant's age ranged from 21 to 34 vears with a mean on 33.3±4.8years. Cervical traction with introduction of cannula and instillation of contrast was found to be the most painful step of the procedure both having a median score of 6 (range 0- 10) based on the NRS and were rated to be moderate to worst possible pain based on the CPS .Almost 65% of the patients perceived the pain to be more than expected and nearly 100% would have preferred one form of analgesia or the other. Conclusion:The most painful step of HSG was found to be the same for the Nigerian women as in other parts of the world.These women should be offered effective analgesia for pain during HSG procedure.